2020
DOI: 10.1097/mao.0000000000002782
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotype of Vestibular Schwannomas

Abstract: Background: Vestibular schwannomas exhibit a uniquely variable natural history of growth, stability, or even spontaneous regression. We hypothesized that a transitory population of immune cells, or immunomodulation of tumors cells, may influence the growth pattern of schwannomas. We therefore sought to characterize the impact of the immune microenvironment on schwannoma behavior. Methods: Forty-eight vestibular schwannomas with preoperative magnetic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…Thus, the recommendation to control tumor growth conservatively with acetyl salicylic acid via COX2 Regarding the preoperative tumor volume, relative higher COX2 expression is associated with larger vestibular schwannoma volume, which was already suggested in our prior study where a correlation of COX2 expression and the tumor extension (Hannover classification) was described [1]. An association of immune cell infiltration and vestibular schwannoma size has also been recently described [2] and could be a possible explanation for this finding. A result that is harder to grasp, is the preoperative tumor volume according to our MIB1 expression results.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Thus, the recommendation to control tumor growth conservatively with acetyl salicylic acid via COX2 Regarding the preoperative tumor volume, relative higher COX2 expression is associated with larger vestibular schwannoma volume, which was already suggested in our prior study where a correlation of COX2 expression and the tumor extension (Hannover classification) was described [1]. An association of immune cell infiltration and vestibular schwannoma size has also been recently described [2] and could be a possible explanation for this finding. A result that is harder to grasp, is the preoperative tumor volume according to our MIB1 expression results.…”
Section: Discussionsupporting
confidence: 63%
“…Department of Neurosurgery, University Hospital Tübingen, Eberhard-Karls-University Tübingen, Hoppe-Seyler Street 3, Tübingen, Germany. 2 Center for Neuro-Oncology, Comprehensive Cancer Center Tübingen -Stuttgart, University Hospital Tübingen, Eberhard-Karls-University Tübingen, Tübingen, Germany. 3 Faculty of Medicine, University of Porto, 4200-319 Porto, Portugal.…”
Section: Availability Of Data and Materialsmentioning
confidence: 99%
“…Consistent with these findings, the levels of macrophage colony-stimulating factor (M-CSF), an important cytokine that stimulates macrophage polarization into an M2-type macrophage, and its synergistic cytokine interleukin-34 (IL-34), are increased in fast-growing VS, suggesting their potential function as promoters of tumor progression (33). Recently, Bi et al demonstrated variable expression of immune regulatory markers as well as immune infiltrates in VS (128). They found both tumor volume and volumetric growth were positively correlated with CD163 expression, and the relationship between PD-L1 and growth strengthened with increasing CD163 infiltration, suggesting a prominent role of immunotherapy in VS treatment (128).…”
Section: Macrophagesmentioning
confidence: 79%
“…Recently, Bi et al. demonstrated variable expression of immune regulatory markers as well as immune infiltrates in VS ( 128 ). They found both tumor volume and volumetric growth were positively correlated with CD163 expression, and the relationship between PD-L1 and growth strengthened with increasing CD163 infiltration, suggesting a prominent role of immunotherapy in VS treatment ( 128 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation